WASTE RECYCLING STRATEGIES IN THE PROCESSING OF RARE AND RADIOACTIVE METALS ORES (International journal of artificial intelligence, 2025)
This article is devoted to strategies for recycling waste generated during the processing of rare and radioactive metal ores. The article analyzes modern methods of waste management, their environmental and economic efficiency. It also discusses scientific and practical approaches to waste recycling, technological innovations and their impact on the environment. The study considers international experiences in waste recycling and the possibilities of their implementation in the conditions of Uzbekistan. The results show the importance of waste recycling strategies in resource conservation and environmental protection.